Tanggung Jawab Penjual Yang Beritikad Tidak Baik Dalam Transaksi Online Dengan Sistem Pembayaran Cash On Delivery - Akyuwen, Rory Jeff (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2023)
Cash on Delivery (COD) systems that do not want the goods that have been ordered to be inspected. a good faith seller will certainly allow the goods to be inspected by the buyer. one of the legal principles in civil law, namely the principle of good faith, requires that every legal action in any form including electronic transactions must be based on good faith. what if it happens that the seller in bad faith deliberately sends goods that are not suitable but the recipient is not allowed to check before being paid. the research method used in this research is normative juridical research type, with 3 (three) approaches namely statutory approach, concept approach and case approach. the results of the research show that the cash on delivery payment system in online buying and selling does not always place the parties, namely the sender/seller and the receiver/buyer in a normal situation. the situation or agreement agreed upon by the parties will cause problems if the goods received are not suitable or damaged. the recipient is required to pay the price of the goods including shipping costs before opening or inspecting the goods. damaged or non-conforming goods can be claimed and if the claim is accepted then the process to replace the goods or pay compensation is carried out.